2012
DOI: 10.1007/s13197-012-0841-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of moisture loss and oil uptake during deep fat frying of Gethi (Dioscorea kamoonensis Kunth) strips

Abstract: Investigation was carried out to study kinetics of moisture loss, oil uptake and tristimulus colour during deep fat frying of Gethi (Dioscorea kamoonensis kunth) strips. Deep fat frying of Gethi strips of size 6 × 6 × 40 mm was carried out in a laboratory scale fryer at different temperatures ranging from 120 to 180 °C. The investigation showed that the moisture loss and oil uptake followed the first order kinetics equation (r > 0.95, p < 0.05). The kinetic coefficients for moisture loss and oil uptake increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 39 publications
(65 reference statements)
8
25
0
2
Order By: Relevance
“…This implies that the frying time is inversely proportional to the moisture content which means that frying time had a significant lowering effect on the moisture content of fried chips. This is in consonance with the work of Manjunatha, who reported an exponential decrease of moisture content of Gethi (Dioscorea kamonensis Kunth) with frying time at varying temperatures [9].…”
Section: Moisture Lossduring Deep Frying Of Raw Yam Chipssupporting
confidence: 92%
See 1 more Smart Citation
“…This implies that the frying time is inversely proportional to the moisture content which means that frying time had a significant lowering effect on the moisture content of fried chips. This is in consonance with the work of Manjunatha, who reported an exponential decrease of moisture content of Gethi (Dioscorea kamonensis Kunth) with frying time at varying temperatures [9].…”
Section: Moisture Lossduring Deep Frying Of Raw Yam Chipssupporting
confidence: 92%
“…Frying was both a cooking and a dehydration process, and it involves simultaneous heat and moisture transfer process in which heat is transferred by the hot oil into the yams during frying and provided enough energy for vaporization of moisture from the yam chips; while oil is absorbed simultaneously [8].During frying process, it is observed that some chemical, physical and sensory characteristics of foods are usually modified. The chemical changes that occurred during this process include gelatinisation of starch, denaturation of protein, enzymes inactivation and flavour development while the physical changes include softening of tissue, decrease in moisture content, increase in oil content, formation of colour, crust and shrinkage and swelling of the product [9]. Figure 1 showed the effect of frying time on moisture content of raw yam chips.…”
Section: Moisture Lossduring Deep Frying Of Raw Yam Chipsmentioning
confidence: 99%
“…However, at lower frying temperature, a * value decreased with increasing frying time and cooking time. The hue angle was smaller compared to the work of Manjuanatha, Ravi, Negi, Raju, and Bawa () who investigate the kinetics of moisture loss and oil uptake in Gethi strips. It was observed that the hue angle decreased with increase in frying temperature and cooking time.…”
Section: Resultsmentioning
confidence: 63%
“…It has been reported that oil absorption is as a result of the microstructural changes caused by deep fat frying, resulting in surface hardening, porosity and pore size distribution [13]. The boiling point of water for the vacuum frying temperatures used was 48 °C so as to ensure that the thermal driving forces were maintained at 60, 70 and 80 °C for both vacuum and atmospheric frying conditions.…”
Section: Oil Uptake (F)mentioning
confidence: 99%